2013
DOI: 10.1245/s10434-013-2910-0
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Specific Codons of the KRAS Oncogene are Associated with Variable Resistance to Neoadjuvant Chemoradiation Therapy in Patients with Rectal Adenocarcinoma

Abstract: Background Mutations in KRAS and TP53 are common in colorectal carcinogenesis and are associated with resistance to therapy. Rectal cancers carrying both mutations are less likely to respond to neoadjuvant chemoradiation therapy (CRT) compared to wildtype tumors. Codon-specific KRAS mutations are associated with variable resistance to targeted therapies, but their association with rectal cancer response to CRT remains unclear. Our objective was to establish a correlation between specific KRAS mutations and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
69
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 24 publications
(30 reference statements)
5
69
2
2
Order By: Relevance
“…In contrast, only 37 % of patients with any other KRAS mutation harbored a TP53 mutation. 5 A similar interplay between KRAS mutation and TP53 mutation was noted by Bazan et al 17 where the presence of TP53 mutations in the L3 domain in combination with KRAS mutations at codon 13 were predictive of worse prognosis in colorectal cancers. We surmise that, in the absence of pathway addiction by a driver mutation and specific targeting of the addicted pathway with a selective inhibitor, individual mutations in genes (passengers) may exert effects on treatment that are a consequence of their inherent ability to drive proliferative prosurvival pathways or occur in a context of other genetic defects that they either interact with or are overshadowed by to elicit a response to treatment.…”
supporting
confidence: 55%
See 2 more Smart Citations
“…In contrast, only 37 % of patients with any other KRAS mutation harbored a TP53 mutation. 5 A similar interplay between KRAS mutation and TP53 mutation was noted by Bazan et al 17 where the presence of TP53 mutations in the L3 domain in combination with KRAS mutations at codon 13 were predictive of worse prognosis in colorectal cancers. We surmise that, in the absence of pathway addiction by a driver mutation and specific targeting of the addicted pathway with a selective inhibitor, individual mutations in genes (passengers) may exert effects on treatment that are a consequence of their inherent ability to drive proliferative prosurvival pathways or occur in a context of other genetic defects that they either interact with or are overshadowed by to elicit a response to treatment.…”
supporting
confidence: 55%
“…4 In the present study, the authors explore this issue further by asking (1) whether the type of KRAS mutation has an impact on predicting treatment outcomes and (2) whether there are any notable associations between KRAS and TP53 mutations that might explain the heterogeneity of treatment responses observed. 5 We consider these two questions separately below.Not all KRAS mutations are created equal. As noted by the authors in the accompanying manuscript, even though the native amino acid at both these codon loci (12 and 13) is glycine, missense mutations result in amino acids as varied as aspartate, valine, alanine, cysteine, and serine.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent data would seem to reinforce the role played by the wt p53 gene (not its protein expression) in determining complete response (CR) to NCRT. Conversely, its mutation, especially in combination with other gene mutations, is probably associated with resistance, 19,20 a finding confirmed by the fact that p53-mutated tumor cells tend to accumulate during chemoradiotherapy. 21 Because it has been shown that rat sarcoma viral oncogene enhances radioresistance in vitro, numerous groups have analyzed Kirsten RAS (KRAS) mutations in pretherapy rectal biopsies in relation to response to NCRT, and reported discordant results.…”
Section: Dna Alterationsmentioning
confidence: 89%
“…24 Although these results should be interpreted with caution because of the many biases, other more recent studies came to similar conclusions, and confirmed an association between KRAS mutations and resistance to NCRT. 20,25 In particular, Duldulao et al performed KRAS and p53 genotyping in 148 patients, and showed that tumors with any KRAS mutation were less likely to have a pCR than those with wt KRAS (P ¼ .006). Moreover, a concurrent p53 mutation was often identified in patients with codon 13 KRAS mutation, whereas mutations in other KRAS codons were associated with a lower frequency of p53 mutation.…”
Section: Dna Alterationsmentioning
confidence: 99%